Health-Related Quality of Life of Type 2 Diabetes Mellitus Outpatients at Dr. Sardjito Hospital, Yogyakarta, Indonesia: An Insulin-Based Therapy Approach - Lolita Lolita; Tri M. Andayani (Indonesian Journal of Clinical Pharmacy, 2017)
Diabetes mellitus type 2 is a lifelong disease which needs an intensive therapy to maintain stable blood sugar levels. Insulin has been proven as an effective treatment modality for type 2 diabetes mellitus patient. The main aim of this research was to evaluate the effect of insulin based therapy (insulin monotherapy-combination therapy of insulin with oral hypoglycemic agents) towards the health related quality of life in type 2 diabetes mellitus outpatient at Dr. Sardjito Hospital, Yogyakarta. This study is a descriptive cross-sectional study design without control. The methods of collecting data includes conducting questionnaires, interviews and examining medical records of patient. Data were taken concurrently from patients who visited Endocrinology Clinic of Dr. Sardjito Hospital from July 2012 until April 2013. Inclusion criteria for the participant were as follows: participant was a type 2 diabetes mellitus outpatient with insulin based therapy, had no languange barrier and was able to participate the study. Participants were excluded in this study if they had a mental and language retardation, uncomplete medical records, and was a pregnant woman. The quality of life was measured by Diabetes Quality of Life Clinical Trial Quessionnaire (DQLCTQ). The statistical analysis used in this study was Mann‑Whitney for QoL analysis based on the type of therapy (insulin monotherapy and combination therapy of insulin-oral hypoglycemic agents). The results from 137 patients shown that patients who received combination therapy had the largest percentage (73%) while the smallest percentage (27%) were single therapy. Whereas, the type of therapy (insulin monotherapy-combination therapy of insulin with oral hypoglycemic agent) significantly influenced the energy domain (p=0,027).Keywords: Health related quality of life, insulin based therapy, type 2 diabetes mellitusKualitas Hidup Terkait Kesehatan dari Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Umum Pusat Dr. Sardjito, Yogyakarta, Indonesia: Suatu Pendekatan Terapi Berbasis InsulinDiabetes melitus tipe 2 adalah penyakit yang membutuhkan terapi intensif seumur hidup untuk menjaga kestabilan kadar gula darah. Insulin terbukti menjadi salah satu modalitas pengobatan yang efektif bagi pasien diabetes melitus tipe 2. Tujuan utama penelitian ini adalah mengevaluasi perbedaan terapi berbasis insulin (terapi insulin dengan atau tanpa agen hipoglikemik oral) terhadap domain kualitas hidup terkait kesehatan pada pasien rawat jalan diabetes melitus tipe 2 di RSUP Dr. Sardjito, Yogyakarta. Penelitian ini merupakan penelitian deskriptif cross-sectional tanpa kontrol. Metode pengumpulan data meliputi wawancara, pengambilan kuesioner dan pemeriksaan rekam medis pasien. Data diambil secara konkuren terhadap pasien yang berkunjung ke Polikinik Endokrinologi RSUP Dr. Sardjito mulai bulan Juli 2012 sampai April 2013. Kriteria inklusi antara lain penderita rawat jalan tipe 2 dengan terapi berbasis insulin, tidak memiliki keterbatasan bahasa dan bersedia berpartisipasi dalam penelitian. Kriteria eksklusi meliputi pasien yang mengalami keterbelakangan mental dan bahasa, catatan medis yang tidak lengkap dan wanita hamil. Pengukuran kualitas hidup menggunakan kuesioner dari Diabetes Quality of Life Clinical Trial Quessionnaire (DQLCTQ). Analisis statistik perbedaan jenis terapi berbasis insulin terhadap domain kualitas hidup pasien menggunakan uji statistik Mann-Whitney. Diperoleh responden sebanyak 137 orang di mana 73% pasien memperoleh terapi kombinasi sedangkan sisanya 27% mendapatkan terapi tunggal yang berbasis insulin. Kesimpulan penelitian ini yaitu perbedaan jenis terapi (monoterapi insulin versus kombinasi insulin dengan agen hipoglikemik oral) secara signifikan memengaruhi domain energi pada kualitas hidup (p=0,027).Kata kunci: Kualitas hidup terkait kesehatan, terapi berbasis insulin, diabetes melitus tipe 2